High‐dose intravenous steroid regimen for radiation‐induced hypoglossal nerve palsy. Issue 2 (5th October 2016) - McDowell, Lachlan J.; Jacobson, Marlene C.; Levin, Wilfred
Abstract: Background: Hypoglossal nerve palsies are infrequent complications of head and neck radiotherapy. Treatments focus on maintaining function and prevention of abnormal airway‐related swallowing events. Methods: A patient with longstanding cranial neuropathies, including bilateral hypoglossal involvement, secondary to chemoradiotherapy for nasopharyngeal carcinoma, experienced repeated episodes of life‐threatening complications. Initially, 2 courses of 2 weekly 24‐hour intravenous methylprednisolone (IVMP) infusions were administered 2 years apart. We report the results of a third course comprising 5 weekly cycles. Results: Patient‐reported outcomes revealed significant improvement in swallowing function, speech, and psychosocial status. Airway invasion during swallowing and pharyngeal retention were assessed videofluoroscopically and evaluated using the Penetration‐Aspiration Scale (PAS) and a residue rating scale, respectively. PAS ratings after infusions 2 and 5, improved dramatically from baseline and were maintained at 1‐year follow‐up. Conclusion: High doses of IVMP may improve radiation‐induced neuropathies. Further testing in similar patients is needed to prove reproducibility. © 2016 Wiley Periodicals, Inc. Head Neck 39: E23–E28, 2017